2015
DOI: 10.1016/j.mce.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of dietary phytoestrogens in adult male rats affects hypothalamic regulation of food intake, induces obesity and alters glucose metabolism

Abstract: A B S T R A C TThe absence of phytoestrogens in the diet during pregnancy has been reported to result in obesity later in adulthood. We investigated whether phytoestrogen withdrawal in adult life could alter the hypothalamic signals that regulate food intake and affect body weight and glucose homeostasis.Male Wistar rats fed from conception to adulthood with a high phytoestrogen diet were submitted to phytoestrogen withdrawal by feeding a low phytoestrogen diet, or a high phytoestrogen-high fat diet. Withdrawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 56 publications
(68 reference statements)
2
21
1
Order By: Relevance
“…(2001) reported that Sprague-Dawley rats fed an AIN-93 based diet with a soy protein isolate replacing casein from conception had lower body weights than the animals fed the casein diet. Andreoli et al (2015) also reported that feeding adult male Wistar rats a low phytoestrogen diet induced obesity and impaired glucose metabolism. Conversely, exposure of Wistar rats to a soy meal-containing diet during development has been reported to result in increased adult body weight in males, but not females (Cao et al, 2015), while developmental exposure of Sprague-Dawley rats to genistein was reported to result in obese adult females, but not males (Strakovsky et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…(2001) reported that Sprague-Dawley rats fed an AIN-93 based diet with a soy protein isolate replacing casein from conception had lower body weights than the animals fed the casein diet. Andreoli et al (2015) also reported that feeding adult male Wistar rats a low phytoestrogen diet induced obesity and impaired glucose metabolism. Conversely, exposure of Wistar rats to a soy meal-containing diet during development has been reported to result in increased adult body weight in males, but not females (Cao et al, 2015), while developmental exposure of Sprague-Dawley rats to genistein was reported to result in obese adult females, but not males (Strakovsky et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Inbred Wistar strain rats were bred at the Department of Human Physiology (Santa Fe, Argentina) and housed under a controlled environment (22°C ± 2°C; lights on from 06:00 to 20:00 h) with free access to pellet laboratory chow (16-014007 Rat-Mouse Diet, Nutrición Animal, Santa Fe, Argentina) and tap water. For more information regarding the food composition, see Kass et al (2012) and Andreoli et al (2015). To minimize additional exposure to EDCs, rats were housed in stainless steel cages with sterile pine wood shavings as bedding, and tap water was supplied in glass bottles with rubber stoppers surrounded by a steel ring.…”
Section: Animalsmentioning
confidence: 99%
“…The animals were maintained in a controlled environment (22 ± 2°C; 14 h of light from 06:00 h to 20:00 h) and had free access to pellet laboratory chow (16-014007 Rat-Mouse Diet, Nutrición Animal, Santa Fe, Argentina). For more information regarding the food composition, see Kass et al (2012), Andreoli et al (2015) and Supplementary Table S1. To minimize additional exposure to EDCs, the rats were housed in stainless steel cages with sterile pine wood shavings as bedding, and glass bottles with rubber stoppers were used to supply drinking water and oral treatments.…”
Section: Animalsmentioning
confidence: 99%